Characterization and evolutionary diversification of the phospholipase D gene family in mosses - Zhao, Jinjie; Pu, Xinyuan; Li, Wenfei; Li, Meng (Frontiers in Genetics, 2022)
Plant phospholipase D (PLD) exerts important roles in various biological processes, such as intracellular signaling and morphological development. Our knowledge about early land plant PLDs is still underdeveloped. In this study, we identified 84 PLD genes in six mosses, i.e., Physcomitrella patens, Ceratodon purpureus, Fontinalis antipyretica, Pleurozium schreberi, Sphagnum magellanicum, and Sphagnum fallax. These PLDs were classified into four clades (I–IV). We showed that PLD underwent rapid expansion in mosses. A total of six conserved domains and two core HKD motifs were detected. Structure analysis uncovered that the moss PLDs from within a clade generally exhibited similar exon-intron organization. Cis-elements prediction and expression analyses indicated that P. patens PLDs had key roles in stress responsiveness and plant development. Particularly, about half of the P. patens PLDs (e.g., PpPLD1, PpPLD2, and PpPLD5) were differentially expressed under biotic and abiotic stresses. We also determined the expression pattern of P. patens PLD genes in various tissues and at different stages of development. Although the moss, clubmoss, liverwort, and fern PLDs evolved largely under functional constraints, we found episodic positive selection in the moss PLDs, e.g., C. purpureus PLD2 and P. patens PLD11. We infer that the evolutionary force acting on the PLDs may have facilitated moss colonization of land. Our work provides valuable insights into the diversification of moss PLD genes, and can be used for future studies of their functions.